Telegram Bot Implementation in Academic Information Services with The Forward Chaining Method - Rianto, Rianto; Rahmatulloh, Alam; Firmansah, Teguh Anugrah (Politeknik Ganesha Medan, 2019)
Academic information is an important information for students in assisting academic activities, every effort has been developed to improve academic services. With the continuous development of various mobile devices or smartphones, the traditional way of Short Message Service (SMS) has been replaced by instant messaging applications that make the communication process more real-time. So this research will try to use technology in instant message as a means of academic service information, it is expected academic information can be delivered more quickly and up-to-date. Telegram as one of the instant messaging application that offers various advantages in its feature than other instant messaging application. The most popular feature and is being developed on telegram is the bot feature, where a third party or user can develop bot features according to user requirements. Thus telegram can help overcome various problems such as academic information seeking problems. For that made the application of lecture information service using Telegram Bot. The making of this information service application is built with Rational Unified Process (RUP) process model, Forward Chaining method and using Python Telepot Framework for Telegram Bot API for application to run via Telegram instant message. With the making of this application, facilitate communication and delivery of academic information to lecturers, students, and the academic community.